Pengaruh Model Guided Discovery Learning Terhadap Penguasaan Konsep Pada Materi Kulit Dan Jaringan Penunjang, Mahasiswa Pendidikan Dokter-Universitas Islam Sumatera Utara - Zaim Anshari (Universitas Islam Sumatera Utara, 2020)
Mastery of concepts is one of the goals of carrying out learning activities for someone, to understand and understand an object or objects through observation and someone's experience in solving problems, so that mastery of this concept becomes a concept that is not easily lost / erased. Therefore, the purpose of this study was to determine whether the guided discovery learning model had an effect on students' mastery of concepts. The sample used was 30 students of Medical Education, Islamic University of North Sumatra. The instrument used is a description test item which consists of five questions. The results of this study indicate that there is an influence between the application of the guided discovery learning model on students' mastery of the concept.